Activity of beta-galactosidase in soil continuously supplemented with lactose - Rysavý, P (Folia microbiologica, 1981)
The microflora of the chernozem soil mineralized 62% of the lactose retained on a column consisting of three 10-g layers of the soil at a daily flow of 48 mg of the sugar. Only 45% of the sugar was mineralized when the daily flow was 136 mg. The highest value of the beta-galactosidase activity in the system of heterocontinuous cultivation was two-fold with respect to batch cultivation. At a higher sugar concentration the enzyme activity in steady state was the same in the whole soil column. This value was reached first in the middle layer of the soil. At a lower concentration of the flowing sugar in steady state the highest enzyme activity was detected in the middle layer of the soil. In the upper layer the enzyme activity was one half, in the lower layer it began to decrease after reaching its maximum after 4 d of the incubation.
Keywords: Galactosidases; beta-Galactosidase; houby; laktosa; Bacteria; beta-galaktosidasa; Soil Microbiology; galaktosidasy; Fungi; půdní mikrobiologie; Lactose